Dampak Program GEMAR dalam Pendampingan Pemberdayaan Perempuan Rawan Sosial Ekonomi di Kelurahan Belawan Bahari Kecamatan Medan Belawan (Tunas Geografi, 2019)
AbstractThe purpose of this study was to find out how much the impact was felt directly and related to the positive impact of the GEMAR program in assisting the empowerment of socio-economic prone women in Belawan Bahari Village, Medan Belawan District. This type of research is descriptive research that is analyzed quantitatively. Sampling techniques using the formula N = n, the sample in this study were 30 respondents, namely women who received the benefits of the GEMAR program. This research instrument uses a questionnaire distributed to 30 respondents. The data obtained tabulated into the table is then analyzed and processed quantitative data by analysis of Case Processing Summary and Test of Normality that before and after the GEMAR program valid data amounts to 30 and no data is missing with a percentage of 100% and significance values before the program GEMAR is 0.083 and after the GEMAR program is 0.719 and greater than 0.05, the two data are declared to be normally distributed. Paired Sample Statistics analysis, Paired Samples Correlation and Paired Samples Test analysis. Based on the results of Paired Sample Statistics analysis after the GEMAR program is higher than before the GEMAR program with an average value before = 35.97 and after average value = 47.20 from 30 data, the results of Paired Samples Correlation analysis that the correlation value before and after the GEMAR program, which produces a number 0.622 with a probability value (Sig.) 0,000 that the correlation between before and after the GEMAR program relates strongly and positively, because the probability value is